CHD4 is a RanGTP-dependent MAP that stabilizes microtubules and regulates bipolar spindle formation - Yokoyama, Hideki; Krijgsveld, Jeroen; Mattaj, Iain W. (Current biology, 2013)
Background - Production of the GTP-bound form of the Ran GTPase (RanGTP) around chromosomes induces spindle assembly by activating nuclear localization signal (NLS)-containing proteins. Several NLS proteins have been identified as spindle assembly factors, but the complexity of the process led us to search for additional proteins with distinct roles in spindle assembly. - Results - We identify a chromatin-remodeling ATPase, CHD4, as a RanGTP-dependent microtubule (MT)-associated protein (MAP). MT binding occurs via the region containing an NLS and chromatin-binding domains. In Xenopus egg extracts and cultured cells, CHD4 largely dissociates from mitotic chromosomes and partially localizes to the spindle. Immunodepletion of CHD4 from egg extracts significantly reduces the quantity of MTs produced around chromatin and prevents spindle assembly. CHD4 RNAi in both HeLa and Drosophila S2 cells induces defects in spindle assembly and chromosome alignment in early mitosis, leading to chromosome missegregation. Further analysis in egg extracts and in HeLa cells reveals that CHD4 is a RanGTP-dependent MT stabilizer. Moreover, the CHD4-containing NuRD complex promotes organization of MTs into bipolar spindles in egg extracts. Importantly, this function of CHD4 is independent of chromatin remodeling. - Conclusions - Our results uncover a new role for CHD4 as a MAP required for MT stabilization and involved in generating spindle bipolarity.
Gesehen am 26.07.2021